Parents' Goals for ADHD Care in a Clinical Pediatric Sample. (September 2014) - McGoron, Lucy; Sturner, Raymond; Howard, Barbara; Barry, Tammy D.; Seymour, Karen; Tomeny, Theodore S.; Morrel, Tanya M.; Ellis, Brandi M.; Marks, Danielle
Objective . This report describes goals parents have for their children with attention deficit/hyperactivity disorder (ADHD) when coming for a pediatric visit. Method . Data were collected from 441 parents of children presenting to either a primary care pediatric practice or a developmental behavioral pediatric practice. Parents were asked to report their top 1 or 2 goals for improvement for their children, and responses were coded into 17 categories. These categories were further grouped into 7 goal composites and examined in relation to demographic characteristics of the families, office type, and symptomology. Results . Goals related to reducing symptoms of inattention were most common, but goals were heterogeneous in nature. Goals were meaningfully, but modestly, related to symptomology. In several instances, symptoms of comorbid conditions interacted with symptoms of ADHD in relation to specific goals being reported. Conclusions . Parents' goals extended beyond ADHD symptoms. Pediatricians need an array of resources to address parents' goals.